An overview of the inventory management system of BBS Cables Limited: how does the IT department maintain its inventory - Shawkat, Muhammad Abul Hasanat Ibn (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.